Familial hypocalcaemia – think about calcium sensor receptor (CASR). (24th May 2012) - Finn, D; Yaw, S How; Mathew, V; Prescott, K; Gupta, S
Abstract : Aim: Activating mutations of CaSR gene have been shown to cause hypercalciuric hypocalcaemia1 . The CaSR plays a key role in maintaining calcium homeostasis by regulating parathyroid hormone (PTH) and renal calcium reabsorption. Activating mutation of CaSR causes increased sensitivity to Ca++ and hence down regulation of PTH secretion. Method: This is a case series where we report a pedigree with clinical picture consistent with familial autosomal dominant hypoparathyroidism. The proband, an 18-month-old girl was found to have incidental hypocalcaemia. We identified 4 other affected individuals in the family, including the father of the proband and his twin brother. All affected individuals had mild hypocalcaemia, low normal serum parathyroid levels and borderline high phosphate levels. Treatment with vitamin D and oral calcium did not improve their serum calcium levels. The father of proband has shown evidence of hypercalciuria and has recently been treated for urolithiasis. Mutation analysis identified a novel activating mutation of the CaSR gene [c.407C>T (p.Pro136Leu)] in all 3 family members who were tested. Conclusion: Activating mutation of the CaSR inhibits PTH secretion and renal calcium reabsorption despite hypocalcaemia. Treatment with vitamin D and calcium can increase hypercalciuria leading to nephrocalcinosis and renal impairment1, 2 . Asymptomatic individuals should not be overtreated in an attempt to normalise serum calcium.